Possibilities of Creating Net Zero Carbon Emissions Cultural Buildings: A Case Study of the Museum at Eleutherna, Crete, Greece - Vourdoubas, John (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Mitigation of climate change requires the reduction of carbon emissions in all human activities including in energy use in buildings. Creation of low or near zero CO2 emissions buildings due to energy use is currently achievable since the required sustainable energy technologies are mature, reliable and cost-effective. The present work is focused on the creation of zero carbon emissions cultural buildings with reference to the museum in Eleutherna, Crete, Greece. Past research regarding the increase of energy efficiency in museum buildings as well as the use of renewable energy technologies in them has been reviewed. Use of solar photovoltaic energy for electricity generation and ground source heat pumps for air-conditioning in order to cover all the annual energy requirements in the museum has been suggested. The proposed renewable energy technologies are well known and cost-effective. The covered area of the museum is 1,800 m2 and its annual energy requirements have been estimated at 216,000 KWh. The size of the required solar-PV system has been calculated at 144 KWpeak; for the ground source heat pump, it is 123.2 KW. The total cost of the sustainable energy systems has been estimated at 290.58 €/m2 for its covered surface while the annual CO2 emissions savings is 162 tonsCO2. The results of the current work indicate that zeroing carbon emissions due to operational energy use in museum buildings is currently feasible with the use of mature, reliable and cost-effective renewable energy technologies.